Inclusive and Collaborative Governance under Vietnam’s New Two-Tier Local Government Model: The Education Sector - Chung Thi Kim Nguyen (Indonesian Association for Public Administration, 2026)
From July 1, 2025, Vietnam will replace its three-tier local government structure with a two-tier model, raising questions about how far legal decentralization can deliver more inclusive and collaborative governance in key sectors such as education. This article uses doctrinal legal analysis to examine the constitutional, organization- al, and fiscal architecture of the reform, focusing on the education decentralization decrees issued by the government. It asks how the two-tier model reallocates powers across the center, province, and commune, whether finance, performance indicators, and data governance rules are aligned with subsidiarity, fiscal equivalence, and trans- parent multilevel coordination, and which combinations of rules create a real scope for collaboration. The analysis finds that inclusive collaboration is most likely where devolved mandates are matched by predictable, equalized funding, clearly specified Education Management Information System (EMIS)-based information flows, and enforceable participation procedures, while ambiguous oversight clauses and frag- mented data systems risk precautionary recentralization, especially in capacity-con- strained provinces. The article concludes by proposing doctrinal benchmarks and a phased implementation roadmap to help policymakers translate the two-tier reform from formal devolution into operational collaboration in the education sector.